Circular Thinking In A Technological Age: Designing For A Regenerative Future - Berawi, Mohammed Ali; Miraj, Perdana; Sari, Mustika (UI Scholars Hub, 2025)
Architecture, engineering, and construction sector is experiencing challenges related to environment and economic aspects. It consumes vast amounts of resources and energy and contributes heavily to global carbon emissions. Academics and industry leaders are trying to explore various strategies to combat climate change by shifting toward circularity. It is a systems-based approach that prioritizes regenerative design, responsible consumption, and closed-loop resource use. At the heart of this shift lies the interplay between circularity, technology, and the environment that can reshape how we live, produce, and consume. But this transformation is not simply about adopting greener practices; it’s about rethinking the role of innovation in creating systems that can sustain our lives. Circular economy (CE) is not just a sustainability trend; it is an emerging as a smart business model that balances environmental responsibility with sufficient profitability. It challenges businesses and cities alike to ask: how can we design products that are repairable, cities that are resource-aware, and systems that regenerate rather than deplete? Just as